2017
DOI: 10.7150/jbji.20425
|View full text |Cite
|
Sign up to set email alerts
|

Management of Asymptomatic Bacteriuria, Urinary Catheters and Symptomatic Urinary Tract Infections in Patients Undergoing Surgery for Joint Replacement: A Position Paper of the Expert Group 'Infection' of swissorthopaedics

Abstract: In this position paper, we review definitions related to this subject and the corresponding literature. Our recommendations include the following statements. Asymptomatic bacteriuria, asymptomatic leukocyturia, urine discolouration, odd smell or positive nitrite sediments are not an indication for antimicrobial treatment. Antimicrobial treatment of asymptomatic bacteriuria does not prevent periprosthetic joint infection, but is associated with adverse events, costs and antibiotic resistance development. Urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…7,31 Studies investigating the necessity of treating ASB before total joint arthroplasty have found no decrease in the risk of infection with such treatment. 9,32 In our study cohort, the fraction of patients receiving preoperative treatment for ASB was similar in the PVI and non-PVI groups (25% vs. 23.7%). However, the preoperative treatment protocol for ASB was neither mandatory nor randomized.…”
Section: Discussionmentioning
confidence: 72%
“…7,31 Studies investigating the necessity of treating ASB before total joint arthroplasty have found no decrease in the risk of infection with such treatment. 9,32 In our study cohort, the fraction of patients receiving preoperative treatment for ASB was similar in the PVI and non-PVI groups (25% vs. 23.7%). However, the preoperative treatment protocol for ASB was neither mandatory nor randomized.…”
Section: Discussionmentioning
confidence: 72%
“…At this time, the American Academy of Orthopedic Surgeons recommends preoperative urine testing prior to elective TJA, but they state that the evidence is weak regarding bacteriuria and negative outcomes 12) . Testing for and treating asymptomatic urinary colonization before orthopedic joint replacement surgery is likely unnecessary and may put the patient at additional risk 10 19 20) . In addition, treating ASB can be associated with adverse outcomes such as increased antibiotic resistance, adverse drug side effects, and unnecessary supply and personnel costs 9) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have found that bacteria causing prosthetic joint infection are not the same as those producing AB [ 128 , 129 ]. Therefore, most societies advocate not screening for or treating AB in these patients [ 1 , 21 ••, 41 , 130 ].…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%